Real-Time Smoke Rendering Using Compensated Ray Marching - Zhou, Kun; Ren, Zhong; Lin, Steve; Bao, Hujun; Guo, Baining; Shum, Harry (2007)
We present a real-time algorithm called compensated ray marching for rendering of smoke under dynamic low-frequency environment lighting. Our approach is based on a decomposition of the input smoke animation, represented as a sequence of volumetric density fields, into a set of radial basis functions (RBFs) and a sequence of residual fields. To expedite rendering, the source radiance distribution within the smoke is computed from only the low-frequency RBF approximation of the density fields, since the high-frequency residuals have little impact on global illumination under low-frequency environment lighting. Furthermore, in computing source radiances the contributions from single and multiple scattering are evaluated at only the RBF centers and then approximated at other points in the volume using an RBF-based interpolation. A slice-based integration of these source radiances along each view ray is then performed to render the final image. The high-frequency residual fields, which are a critical component in the local appearance of smoke, are compensated back into the radiance integral during this ray march to generate images of high detail. The runtime algorithm, which includes both light transfer simulation and ray marching, can be easily implemented on the GPU, and thus allows for real-time manipulation of viewpoint and lighting, as well as interactive editing of smoke attributes such as extinction cross section, scattering albedo, and phase function. Only moderate preprocessing time and storage is needed. This approach provides the first method for real-time smoke rendering that includes single and multiple scattering while generating results comparable in quality to offline algorithms like ray tracing.